Carbonaceous Materials-Based Electric Double Layer Capacitors with Improved Electrochemical Performance - Zhu, Lei; Ali, Asghar; Ye, Shu; Ulla, Kefayat; Yuan, Chang-Zhou; Kim, Ick-Jun; Yang, Sun-Hye; Oh, Won-Chun (Asian Journal of Chemistry, 2015)
In this study, the fabrication of working electrodes was carried out as follows. Briefly, the electrodes were composed of graphene as an active material, Ketjen black and activated carbon fiber as an electric conductor and polytetrafluoroethylene [(C2F4)n, PTFE] as a binder. The prepared electrodes were characterized by X-ray diffraction and scanning electron microscopy. Finally, the electrochemical performances of carbon materials in the electrolyte solution of tetraethylammonium tetrafluoroborate [(C2H5)4NBF4, TEABF4] in propylene carbonate were examined. The graphene nanosheets electrode in the work exhibited a good rate of capability and reversibility at high scan rates in electrochemical performances.